2018
DOI: 10.1111/ajt.14594
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-term outcomes in renal allografts with deceased donors: A large recipient and donor genome-wide association study

Abstract: Improvements in immunosuppression have modified short‐term survival of deceased‐donor allografts, but not their rate of long‐term failure. Mismatches between donor and recipient HLA play an important role in the acute and chronic allogeneic immune response against the graft. Perfect matching at clinically relevant HLA loci does not obviate the need for immunosuppression, suggesting that additional genetic variation plays a critical role in both short‐ and long‐term graft outcomes. By combining patient data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 35 publications
0
49
0
Order By: Relevance
“…18 Genotyping details for the Dublin and Tennessee cohorts were described previously. 18 Genotyping details for the Dublin and Tennessee cohorts were described previously.…”
Section: Genotyping Imputation and Data Quality Controlmentioning
confidence: 99%
“…18 Genotyping details for the Dublin and Tennessee cohorts were described previously. 18 Genotyping details for the Dublin and Tennessee cohorts were described previously.…”
Section: Genotyping Imputation and Data Quality Controlmentioning
confidence: 99%
“…6 However, this study was limited by its sample size (n = 326) and an independent effort failed to replicate the findings. 7 Although much better powered than earlier efforts, no significant associations were found beyond the previously known effect of the HLA. 7 Although much better powered than earlier efforts, no significant associations were found beyond the previously known effect of the HLA.…”
Section: Introductionmentioning
confidence: 83%
“…1 A number of studies have examined candidate genes or variants beyond the HLA and their impact on graft function [2][3][4] ; however, few have been replicated. [6][7][8] A study from 2013 identified recipient genotype loci on chromosomes 14 and 18 which significantly associated with 5 years serum creatinine and long-term graft survival. [6][7][8] A study from 2013 identified recipient genotype loci on chromosomes 14 and 18 which significantly associated with 5 years serum creatinine and long-term graft survival.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 recipient genetic loci highlighted in their paper,3 rs10765602 (gene annotation CCDC67 ) and rs7976329 (gene annotation PTPRO ), were well imputed in our study (INFO>0.95) and neither reached genome‐wide significance in our reported analyses 2. To provide additional confidence, we have reanalyzed our data following reimputation to the 1000 Genomes phase 3 reference panel via the Sanger Imputation Service (www.…”
mentioning
confidence: 80%
“…We thank Massart et al for their comments1 on our recently published large‐scale genome‐wide association study of renal transplant outcomes,2 and we welcome the opportunity to examine their findings in more detail.…”
mentioning
confidence: 96%